ZIMBABWE : A Country Profile (Journal of International Studies, 2020)
Zimbabwe is a relatively small country situated in the southern part of Africa between South Africa and Zambia. It is also bounded by Mozambique in the east and Botswana in the West. This land-locked country occupies about 390,757 sq km of land and its population is about 12.4 million (CIA World Fact Book, 2011). Zimbabwe was a British colony for almost a century and was one of a few countries which belatedly achieved independence after waging a protracted liberation war. Several racial and ethnic groups reside in the county. English is the official language with two dominating native languages, that is, Shona and Sindebele being accorded national language status. Since 2000, Zimbabwe has been embroiled in the worst political and socio-economic crisis of its thirty-one year history as an independent state. Unfortunately, this unprecedented crisis has negatively affected every aspect of the country and every segment of the population. However, in February, 2009, after almost a year of uncertainty following controversial elections in 2008, a semblance of normality seems to have emerged after the main political actors agreed to set up an inclusive government. Despite these promising signs the country is still not out of the woods yet.